Upaya Rekonsiliasi Terhadap Timbulnya Potensi Kebijakan Dalam Pengelolaan Organisasi - luhur, M Aji; mustholiq, mustholiq; Ilham, Yusuf; Syafi'i, Imam (universitas teuku umar, 2025)
The purpose of this study is to determine the organization's efforts in carrying out alignment actions to potential policies that occur. Against the background of the loss of paradigm (basic beliefs) to the management of the organization from the concept of strategy that has been planned to be executed. The main problem is insensitivity/lack of organisational data information in assessing risks and obstacles that occur in organisational management that can potentially arise policies. This research is descriptive qualitative research used to determine organizational strategies in aligning with the emergence of potential policies that occur. The conclusion obtained is that the potential for policy is a form of symptom of the unpreparedness of organizational managers in implementing basic elements such as input elements consisting of planning activities to be carried out in achieving the desired final results, process elements used to carry out agreed activity planning towards results according to the desired target and output elements are an achieved result. The misalignment of the three basic elements of organizational management means that organizational management will carry out policies as additional elements that are used as elements to bridge the conditions that occur. The higher potential of policies that occur is an indicator of the inability to manage the organization properly and the smaller the potential for policies that occur is an indicator of readiness to manage the organization because it has an impact on the rise or fall of the level of trust in organizational management. Keywords: work planning, behavior and organizational performance. Policy